Preparation method of pigment dispersing agent and pigment dispersion

A copolymer of light gasoline and maleic anhydride before etherification was prepared by self-stabilizing precipitation polymerization. Polar groups were introduced by hydrolysis or sulfonation modification, which solved the problems of insufficient dispersion performance of pigment dispersants and high olefin content of light gasoline before etherification. This resulted in an efficient pigment dispersion and an economical method for reducing olefin content.

CN120842481APending Publication Date: 2025-10-28BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510940862.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

There is still room for improvement in the dispersion performance of existing pigment dispersants, and the methods used by petroleum refining companies to reduce the olefin content in light gasoline before etherification are not economically viable.

Method used

A self-stabilizing precipitation polymerization method was used to prepare a copolymer of light gasoline and maleic anhydride before etherification. Polar groups of -COOH or -SO3H were introduced by hydrolysis or sulfonation modification to prepare a pigment dispersant with excellent dispersing properties.

Benefits of technology

It improves the dispersion stability and economic benefits of pigment dispersions, achieves dispersions with high pigment solid content, and optimizes the performance of pigment dispersions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120842481A_ABST
    Figure CN120842481A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a pigment dispersant and a pigment dispersion. The preparation method of the pigment dispersant comprises the following steps: (1) carrying out self-stabilization precipitation polymerization on light gasoline before etherification and maleic anhydride in an organic solvent to obtain a mixed olefin-maleic anhydride copolymer; (2) carrying out functional modification on the mixed olefin-maleic anhydride copolymer; wherein the functional modification is (i) hydrolysis modification or (ii) sulfonation modification, (i) hydrolysis modification: hydrolyzing a maleic anhydride group in the mixed olefin-maleic anhydride copolymer, and (ii) sulfonation modification: reacting the mixed olefin-maleic anhydride copolymer with a sulfonic acid compound having a hydroxyl group or an amino group. According to the preparation method of the pigment dispersant, the low-value petrochemical crude product (light gasoline before etherification) is used as the raw material, so that the utilization efficiency of the petrochemical crude product is improved, and the green and environment-friendly concept is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fine chemicals, specifically relating to a method for preparing pigment dispersants and pigment dispersions. Background Technology

[0002] Pre-etherified light gasoline typically refers to light gasoline components that have not undergone etherification treatment. It is primarily composed of C5-C6 olefins and is an intermediate product in the petroleum refining process. This gasoline component can be obtained through processes such as catalytic cracking (FCC). Its main characteristics are high olefin content and high octane potential. The high olefin content, sulfur and nitrogen impurities, and low octane number in pre-etherified light gasoline can affect its storage, combustion performance, and emission standards, and pose potential safety hazards. Petroleum refining companies typically pre-treat pre-etherified light gasoline, such as desulfurization, denitrification, and reducing olefin content, to improve its quality and application value, but production costs and environmental pollution must be considered.

[0003] Pigment dispersants are additives widely used in industries such as coatings and inks. Their main function is to help pigment particles disperse evenly in the base material, prevent pigment particles from agglomerating and settling, thereby improving the performance and stability of the product. The performance of pigment dispersants directly affects the color, gloss, hiding power and other indicators of the final product. Pigment dispersants usually have the following structural characteristics: (1) Anchoring groups. This structure allows the dispersant to be firmly adsorbed onto the surface of pigment particles. They are usually some polar functional groups, such as carboxyl (-COOH), hydroxyl (-OH), amino (-NH2) and sulfonic acid (-SO3H), which are usually based on ionic bonds, hydrogen bonds or van der Waals forces to bind to the surface of pigment particles. (2) Solvation chains. This structure can extend into the continuous phase to form a stable solvation layer. They are usually composed of long hydrocarbon chains or polyoxyethylene (PEO) chains, which usually provide steric hindrance effect to prevent agglomeration between pigment particles.

[0004] Currently, pigment dispersants can be classified into four categories according to their chemical structure and mechanism of action: (1) Anionic dispersants, such as sodium polyacrylate and polycarboxylate, are usually used for the dispersion of polar pigments in aqueous systems; (2) Cationic dispersants, such as quaternary ammonium salts, are usually used for negatively charged pigment surfaces; (3) Nonionic dispersants, such as polyoxyethylene ether and polyoxyethylene ester, are applicable to a variety of pigment or base material systems; (4) Amphoteric dispersants, such as betaine type and amino acid type, usually have good pH adaptability and electrolyte resistance.

[0005] Pigment dispersions are generally composed of pigment particles, dispersion media, and additives. They refer to stable mixtures formed by uniformly dispersing solid pigment particles in a liquid medium. They are important components of industrial products such as coatings and inks, and directly affect the final performance of the products, such as color, hiding power, gloss, and weather resistance. The preparation process of pigment dispersions generally includes three steps: (1) Wetting process: There are intermolecular forces such as van der Waals forces, dispersion forces, or hydrogen bonds between pigment molecules, so pigments are generally in an agglomerated state. When pigments are added to a solution containing a dispersant, the pigment particles are easily wetted by the solution due to the surface activity of the dispersant, and thus are uniformly distributed in the solution. (2) Dispersion process: The dispersion is stirred by mechanical force such as high-speed stirring or ball milling to refine the pigment, increase the specific surface area, and facilitate the adsorption of the dispersant. (3) Stabilization process: Based on the charge repulsion or steric hindrance, the pigment particles adsorbing the dispersant tend to be stably distributed. The performance of pigment dispersions is generally affected by factors such as pigment properties, dispersion medium, dispersant, dispersion equipment, dispersion process, and system pH. Furthermore, their performance is generally evaluated by indicators such as dispersibility, stability, tinting strength, hiding power, and weather resistance.

[0006] Therefore, efficient dispersants are of great significance for the preparation of high-performance pigment dispersions, which are usually characterized by excellent dispersion stability even with high pigment solid content. Summary of the Invention

[0007] The problem the invention aims to solve

[0008] There is still room for improvement in the dispersion performance (dispersion stability) of pigment dispersants in the prior art.

[0009] The current methods used by oil refining companies to reduce the olefin content in light gasoline before etherification still have room for improvement in terms of economic efficiency.

[0010] The purpose of this invention is to provide a method for preparing a pigment dispersant with excellent dispersing properties. It also aims to provide a highly economical method for reducing the olefin content in light gasoline before etherification.

[0011] Solution for solving the problem

[0012] To address the aforementioned issues, the inventors conducted extensive research and proposed a method based on self-stabilizing precipitation polymerization (2SP). This method utilizes the polymerization reaction between maleic anhydride (MAH) and olefins to reduce the olefin content in light gasoline before etherification. Furthermore, the resulting copolymer is modified by introducing functional groups, thereby endowing it with excellent pigment dispersion properties. This achieves the transformation of petrochemical waste into high-value-added functional polymers.

[0013] The pigment dispersant of the present invention uses etherified light gasoline mixed olefin-maleic anhydride copolymer (PUGM) as a precursor, and the anhydride group is hydrolyzed or sulfonated to introduce -COOH or -SO3H polar groups, thereby giving it excellent dispersibility.

[0014] Specifically, the present invention solves the problems of the present invention through the following solutions.

[0015] [1] A method for preparing a pigment dispersant, comprising the following steps:

[0016] (1) The light gasoline before etherification and maleic anhydride are subjected to self-stabilizing precipitation polymerization in an organic solvent to obtain a mixed olefin-maleic anhydride copolymer.

[0017] (2) The mixed olefin-maleic anhydride copolymer is functionalized and modified;

[0018] The functional modification is either (i) hydrolysis modification or (ii) sulfonation modification.

[0019] (i) Hydrolysis modification: hydrolyzing the maleic anhydride groups in the mixed olefin-maleic anhydride copolymer.

[0020] (ii) Sulfonation modification: reacting the mixed olefin-maleic anhydride copolymer with a sulfonic acid compound having hydroxyl or amino groups.

[0021] [2] According to the preparation method described in [1], in the hydrolysis modification, the hydrolysis is carried out in an alkaline aqueous solution, wherein the alkaline is preferably sodium hydroxide and / or potassium hydroxide, and the concentration of the alkaline aqueous solution is 0.1 to 5 mol / L.

[0022] [3] According to the preparation method described in [1], wherein in the sulfonation modification, the sulfonic acid compound having hydroxyl or amino groups is selected from one or more of aminosulfonic acid, alkylaminosulfonic acid, arylaminosulfonic acid, aminoalkylsulfonic acid, aminoarylsulfonic acid, hydroxyalkylsulfonic acid, hydroxyarylsulfonic acid, hydroxyalkylaminosulfonic acid and their salts.

[0023] Preferably, the sulfonic acid compound having a hydroxyl or amino group is selected from one or more of the following: aminosulfonic acid, N-methylaminosulfonic acid, ethylaminosulfonic acid, aminomethanesulfonic acid, taurine, aminopropanesulfonic acid, 2-aminobenzenesulfonic acid, 3-aminobenzenesulfonic acid, 4-aminobenzenesulfonic acid, aminonaphthalenesulfonic acid, (3-hydroxypropyl)aminosulfonic acid, 3-hydroxypropanesulfonic acid, 4-hydroxybutyric acid, 4-hydroxybenzenesulfonic acid, m-hydroxybenzenesulfonic acid, hydroxyethylsulfonic acid, 8-hydroxynaphthalene-1-sulfonic acid, and their salts;

[0024] The molar ratio of maleic anhydride groups in the mixed olefin-maleic anhydride copolymer to the sulfonic acid compound having hydroxyl or amino groups is 1:(0.1-3).

[0025] The reaction of the mixed olefin-maleic anhydride copolymer with a sulfonic acid compound having hydroxyl or amino groups is carried out in an aprotic dipole solvent.

[0026] [4] According to the preparation method described in [1], in step (1), the organic solvent includes an organic acid alkyl ester, which preferably has the following structure:

[0027]

[0028] Wherein R1 is H or a hydrocarbon group having 1 to 8 C atoms, and R2 is an alkyl group having 1 to 5 C atoms;

[0029] Preferably, the organic solvent further includes alkanes, and the mass ratio of the organic acid alkyl ester to the alkanes is 1:(0.1-3).

[0030] [5] According to the preparation method described in [1], in step (1), the mass ratio of maleic anhydride to etherified light gasoline is 1: (1-5);

[0031] The total content of maleic anhydride and pre-etherified light gasoline in the reaction system is 10-50% by mass, where "reaction system" refers to the system composed of maleic anhydride, pre-etherified light gasoline, organic solvent, and initiator.

[0032] [6] A pigment dispersant, which is obtained by any one of the preparation methods described in [1] to [5].

[0033] [7] A pigment dispersion comprising water, an inorganic pigment and a pigment dispersant according to [6].

[0034] [8] According to the pigment dispersion of [7], wherein the content of the inorganic pigment is 50% by mass or more of the pigment dispersion; and the amount of the pigment dispersant is 5% by mass or less of the inorganic pigment.

[0035] [9] The pigment dispersion according to [7] or [8], wherein the inorganic pigment is one or more selected from metal oxides, metal sulfides, chromates, and silicates; preferably one or more selected from the following: iron oxide red, iron oxide yellow, titanium dioxide, cobalt blue, cobalt green, cadmium yellow, cadmium red, chrome yellow, and ultramarine.

[0036]

[10] The pigment dispersion according to [7] or [8] further includes one or more additives selected from the following: defoamer, pH adjuster, antisettling agent.

[0037] The effects of the invention

[0038] The method for preparing the pigment dispersant of the present invention uses low-value petrochemical crude products (light gasoline before etherification) as raw materials, which improves the utilization efficiency of petrochemical crude products and conforms to the concept of green and environmental protection.

[0039] The pigment dispersant of the present invention has superior dispersion performance and stabilization effect compared with commercially available dispersants. Specifically, under the same amount of dispersant and comparable dispersion and stabilization effect, a pigment dispersion with higher pigment solid content can be obtained, which greatly optimizes the performance of the pigment dispersion.

[0040] The pigment dispersion of the present invention has high solid content and excellent dispersion stability. Attached Figure Description

[0041] Figure 1 The hydrodynamic diameter (D) of the dispersion obtained in Reference Examples 5-6 h ) and Zeta potential.

[0042] Figure 2 Photographs of the 48-hour settling experiment of Comparative Example 3, Example 12 and Example 6.

[0043] Figure 3 Images (a) through (d) are transmission electron microscopy (TEM) images of the dispersions of Reference Example 4, Comparative Example 3, Example 6, and Example 12, respectively. Detailed Implementation

[0044] The present invention will now be described in detail. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples.

[0045] <Terminology and Definitions>

[0046] In this manual, "pre-etherified light gasoline" refers to the light fraction of catalytic cracking gasoline that has not undergone etherification treatment.

[0047] In this specification, "self-stabilizing precipitation polymerization" refers to a polymerization method in which the polymerization product is stably dispersed in the system without the use of any stabilizer, using a "static polymerization" approach.

[0048] In this specification, unless otherwise expressly stated, “alkyl” means straight-chain, branched, and cyclic alkyl.

[0049] In this specification, the range of values ​​referred to as "value A to value B" refers to the range including the endpoint values ​​A and B.

[0050] Unless otherwise explicitly stated, "%" in this specification indicates mass or weight percentage.

[0051] In this specification, the numerical range indicated by "above" or "below" refers to the numerical range that includes the stated number.

[0052] In this specification, the word "may" has two meanings: to perform a certain process and not to perform a certain process.

[0053] In this specification, the terms "optionally" or "optionally" are used to indicate the use or non-use of certain substances, components, procedures, application conditions, etc.

[0054] All unit names used in this specification are international standard unit names, and all numerical values ​​and ranges appearing in this invention should be understood to include unavoidable systematic errors in industrial production.

[0055] In this specification, references to "preferred embodiments," "implementation methods," etc., mean that a specific element (e.g., feature, structure, property, and / or characteristic) related to that embodiment is included in at least one of the embodiments described herein, and may or may not be present in other embodiments. Furthermore, it should be understood that the elements may be combined in any suitable manner in various embodiments.

[0056] Unless otherwise expressly stated, the operations described in this manual shall be performed at room temperature (15–35°C).

[0057] <Pigment Dispersants and Their Preparation Methods>

[0058] One object of the present invention is to provide a method for preparing a pigment dispersant, which includes the following steps:

[0059] (1) The light gasoline before etherification and maleic anhydride are subjected to self-stabilizing precipitation polymerization in an organic solvent to obtain a mixed olefin-maleic anhydride copolymer.

[0060] (2) The mixed olefin-maleic anhydride copolymer is functionalized and modified;

[0061] The functional modification is either (i) hydrolysis modification or (ii) sulfonation modification.

[0062] (i) Hydrolysis modification: hydrolyzing the maleic anhydride groups in the mixed olefin-maleic anhydride copolymer.

[0063] (ii) Sulfonation modification: reacting the mixed olefin-maleic anhydride copolymer with a sulfonic acid compound having hydroxyl or amino groups.

[0064] This invention uses etherified light gasoline mixed olefin-maleic anhydride copolymer (PUGM) as a precursor, and hydrolyzes or sulfonates the anhydride groups to introduce -COOH or -SO3H polar groups, thereby giving the pigment dispersant excellent dispersibility.

[0065] In this specification, "pre-etherified light gasoline mixed olefin-maleic anhydride copolymer" and "mixed olefin-maleic anhydride copolymer" have the same meaning.

[0066] The following describes in detail each step of the preparation method of the present invention.

[0067] Step (1)

[0068] In step (1), the mixed olefins in the light gasoline before etherification are copolymerized with maleic anhydride through self-stabilizing precipitation polymerization to obtain a mixed olefin-maleic anhydride copolymer.

[0069] This invention does not impose any particular limitation on the composition of the pre-etherification light gasoline; any industrially suitable pre-etherification light gasoline can be used. Typically, the pre-etherification light gasoline contains C4-C6 olefins, with a total olefin content of 25–60% by mass, predominantly C5 olefins. Specifically, the C4 olefin content is typically 1–5% by mass, for example, 2–4% by mass; the C5 olefin content is typically 20–50% by mass, for example, 25–45% by mass, or even 30–40% by mass; and the C6 olefin content is 1–5% by mass, for example, 1.5–4% by mass.

[0070] More specifically, the C5 olefins in the pre-etherified light gasoline have one or more of the following structures:

[0071]

[0072] Typically, self-stabilizing precipitation polymerization is carried out in the presence of an initiator. The initiator is preferably one or more selected from azo compound initiators and peroxide initiators. Preferably, the peroxide initiator is benzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, dodecyl peroxide, tert-butyl peroxide, diisopropyl peroxide, dicyclohexyl peroxide, etc.; the azo compound initiator is azobisisobutyronitrile (AIBN), azobisisoheptanenitrile, etc. Azobisisobutyronitrile is preferred.

[0073] Preferably, based on the mass of maleic anhydride, the amount of initiator is 0.1 to 10% by mass, more preferably 0.2 to 9% by mass, more preferably 0.3 to 8% by mass, and even more preferably 0.4 to 7% by mass, for example 1% by mass, 2% by mass, 3% by mass, 4% by mass, 5% by mass, and 6% by mass.

[0074] Self-stabilizing precipitation polymerization is carried out in an organic solvent. In some embodiments, the organic solvent comprises an alkyl ester of an organic acid. Preferably, the alkyl ester of the organic acid has the following structure:

[0075]

[0076] R1 is a hydrocarbon group with H or 1 to 8 C atoms, and R2 is an alkyl group with 1 to 5 C atoms.

[0077] Preferably, the organic acid alkyl ester is selected from one or more of the following: ethyl formate, propyl formate, isobutyl formate, amyl formate, ethyl acetate, butyl acetate, isobutyl acetate, amyl acetate, isoamyl acetate, benzyl acetate, phenyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, isobutyl butyrate, isoamyl butyrate, ethyl isobutyrate, ethyl isovalerate, isoamyl isovalerate, methyl benzoate, ethyl benzoate, propyl benzoate, butyl benzoate, isoamyl benzoate, methyl phenylacetate, ethyl phenylacetate, propyl phenylacetate, butyl phenylacetate, isoamyl phenylacetate, ethyl phenylacetate, propyl phenylacetate, butyl phenylacetate, and isoamyl phenylacetate. Organic acid alkyl esters are good solvents, capable of effectively dissolving light gasoline, MAH, and initiators before etherification. Furthermore, the polymerization product PUGM is insoluble in this system; therefore, PUGM can be separated from the system by centrifugation or filtration.

[0078] In some embodiments, the organic solvent includes an alkane, preferably one or more selected from petroleum ether, n-hexane, cyclohexane, n-heptane, octane, isooctane, and isopentane.

[0079] Preferably, in the organic solvent, the mass ratio of organic acid alkyl ester to alkane is 1:(0-3), more preferably 1:(0.1-3), more preferably 1:(0.2-2.5), and even more preferably 1:(0.5-2), for example 1:1 or 1:1.5.

[0080] In some embodiments, the organic solvent contains 25-100% by mass, preferably 30-90% by mass, more preferably 40-80% by mass, and even more preferably 45-70% by mass.

[0081] In some embodiments, the alkane content in the organic solvent is 0-75% by mass, preferably 10-70% by mass, more preferably 20-60% by mass, and even more preferably 30-55% by mass.

[0082] The use of a mixed solvent of organic acid alkyl esters and alkanes is to further adjust the solubility parameters of the solvent system, thereby increasing the reduction rate of olefin content in light gasoline before etherification and the yield of PUGM.

[0083] Preferably, by selecting a solvent, the solubility parameter of the copolymer as the polymerization product is 1 to 7 MPa greater than the solubility parameter of the organic solvent. 1 / 2 Preferably 2-5 MPa 1 / 2 .

[0084] The solubility parameter of a polymer has the conventional meaning in the art and can be calculated indirectly using the contribution values ​​of each group in the molecular structure, by the following formula:

[0085] δ=ρ∑F i / M

[0086] Where δ is the solubility parameter of the polymer; Fi is the molar attraction constant of each functional group in the polymer molecule; ρ is the density of the polymer; and M is the molecular weight of the polymer repeating unit.

[0087] The solubility parameters of solvents can be found in technical manuals or published literature in this field. For example, the solubility parameters of various solvents are recorded in "Polymer Physics" (Hua Youqing, Jin Riguang, Chemical Industry Press, 2013, p. 83).

[0088] Preferably, the mass ratio of maleic anhydride to etherified light gasoline is 1:(1-5), more preferably 1:(1.5-4), for example 1:(2-3).

[0089] Preferably, the total content of maleic anhydride and pre-etherified light gasoline in the reaction system is 10-50% by mass, more preferably 20-40% by mass. The "reaction system" refers to a system composed of maleic anhydride, pre-etherified light gasoline, organic solvent, and initiator.

[0090] In this invention, there are no particular restrictions on the mixing order and method of the components in the reaction system of step (1), and they can be carried out in any suitable manner and order.

[0091] Preferably, after mixing the maleic anhydride and solvent, the pre-etherified light gasoline and initiator are added, so that the resulting reaction system undergoes self-stabilizing precipitation polymerization.

[0092] In some specific embodiments, the polymerization reaction is initiated by heating the reaction system to the polymerization temperature. The polymerization temperature can be 50–120°C, preferably 60–110°C, for example: 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, etc.

[0093] Preferably, the polymerization reaction time is 1 to 24 hours, for example: 2 hours, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours, etc.

[0094] Preferably, the polymerization reaction can be carried out under the protection of an inert gas, specifically, the inert gas can be nitrogen or argon.

[0095] In step (1), all the olefins contained in the pre-etherified light gasoline undergo polymerization with maleic anhydride to obtain copolymers of various olefins and maleic anhydride, hence the name (pre-etherified light gasoline) mixed olefin-maleic anhydride copolymer. Taking n-pentene as an example, its reaction with MAH via self-stabilizing precipitation polymerization to obtain a copolymer is as follows:

[0096]

[0097] In a specific implementation plan, step (1) further includes a post-treatment step of the reaction system after self-stabilizing precipitation polymerization, wherein the post-treatment preferably includes one or more combinations of solid-liquid separation, washing or drying.

[0098] Based on the characteristics of the self-stabilizing precipitation polymerization reaction method, the reaction system obtained after polymerization is a dispersion system of copolymer microspheres. Therefore, no precipitant is needed, and the copolymer microspheres can be separated by solid-liquid separation alone.

[0099] More specifically, after the polymerization reaction, the reaction system is subjected to solid-liquid separation, and optionally the separated solid (polymer microspheres) is dried.

[0100] Solid-liquid separation can be performed using known methods, such as filtration, centrifugation, and solvent evaporation.

[0101] Washing can be carried out by rinsing the separated solids with a washing solvent, dispersing the separated solids in a washing solvent, and then performing solid-liquid separation again.

[0102] Drying can be carried out by methods known in the art, such as evaporating the residual solvent by heating. The drying temperature can be 40–150°C, for example 40–100°C, and the drying time can be 1–48 hours, for example 4–40 hours or 8–30 hours.

[0103] Step (2)

[0104] In step (2), the obtained mixed olefin-maleic anhydride copolymer is functionalized. The functionalization modification is either (i) hydrolysis modification or (ii) sulfonation modification.

[0105] (i) Hydrolysis modification

[0106] Hydrolysis modification is carried out by hydrolyzing the maleic anhydride groups in the mixed olefin-maleic anhydride copolymer.

[0107] Preferably, the hydrolysis is carried out in an alkaline aqueous solution. For example, a mixed olefin-maleic anhydride copolymer is mixed with an alkaline aqueous solution and heated to the hydrolysis reaction temperature to hydrolyze the maleic anhydride groups.

[0108] The mass ratio of the mixed olefin-maleic anhydride copolymer to the alkaline aqueous solution is preferably 1:(5-30), more preferably 1:(8-20).

[0109] Preferably, the alkali is sodium hydroxide and / or potassium hydroxide.

[0110] Preferably, the concentration of the alkaline aqueous solution is 0.1–5 mol / L, more preferably 0.2–4 mol / L, even more preferably 0.3–4 mol / L, even more preferably 0.4–2 mol / L, and even more preferably 0.5–1.5 mol / L, for example 1 mol / L.

[0111] Preferably, the hydrolysis reaction is carried out at 50–90°C, more preferably at 60–80°C.

[0112] Preferably, the hydrolysis reaction takes 2 to 6 hours, and more preferably 3 to 5 hours.

[0113] The hydrolysis reaction of the copolymer of n-pentene and maleic anhydride illustrated above is as follows:

[0114]

[0115] Optionally, a precipitant is added to the reaction mixture after the hydrolysis reaction to precipitate the polymer, and the precipitate is then optionally washed and dried.

[0116] Precipitating agents can be poor solvents such as methanol, ethanol, propanol, and isopropanol.

[0117] Optionally, the obtained pigment dispersant is ground after hydrolysis modification.

[0118] (ii) Sulfonation modification

[0119] Sulfonation modification is carried out by reacting the maleic anhydride groups in the mixed olefin-maleic anhydride copolymer with sulfonic acid compounds having hydroxyl or amino groups.

[0120] Preferably, the sulfonic acid compound having a hydroxyl or amino group is one or more selected from aminosulfonic acid, alkylaminosulfonic acid, arylaminosulfonic acid, aminoalkylsulfonic acid, aminoarylsulfonic acid, hydroxyalkylsulfonic acid, hydroxyarylsulfonic acid, hydroxyalkylaminosulfonic acid, and their salts.

[0121] More preferably, the sulfonic acid compound having a hydroxyl or amino group is selected from one or more of the following: aminosulfonic acid, N-methylaminosulfonic acid, ethylaminosulfonic acid, aminomethanesulfonic acid, taurine, aminopropanesulfonic acid, 2-aminobenzenesulfonic acid, 3-aminobenzenesulfonic acid, 4-aminobenzenesulfonic acid, aminonaphthalenesulfonic acid, (3-hydroxypropyl)aminosulfonic acid, 3-hydroxypropanesulfonic acid, 4-hydroxybutyric acid, 4-hydroxybenzenesulfonic acid, m-hydroxybenzenesulfonic acid, hydroxyethylsulfonic acid, 8-hydroxynaphthalene-1-sulfonic acid, and their salts. The salts are alkali metal salts or alkaline earth metal salts, preferably sodium, potassium, lithium, or magnesium salts.

[0122] Preferably, the molar ratio of maleic anhydride groups in the mixed olefin-maleic anhydride copolymer to the sulfonic acid compound having hydroxyl or amino groups is 1:(0.1-3), more preferably 1:(0.2-2.5), more preferably 1:(0.3-2), even more preferably 1:(0.4-1.8), and even more preferably 1:(0.5-1.5), for example 1:1.

[0123] Preferably, the reaction of the mixed olefin-maleic anhydride copolymer with a sulfonic acid compound having hydroxyl or amino groups is carried out in an aprotic dipole solvent. The aprotic dipole solvent is preferably at least one selected from dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetonitrile, N-methylpyrrolidone, ethylene carbonate, propylene carbonate, dimethyl lactamide, sulfolane, and dihydro-L-glucanone.

[0124] Preferably, the reaction temperature for sulfonation modification is 60–100°C, more preferably 70–90°C.

[0125] Preferably, the sulfonation reaction time is 2 to 20 hours, more preferably 3 to 15 hours, more preferably 4 to 12 hours, and even more preferably 5 to 10 hours.

[0126] The sulfonation modification of the copolymer of n-pentene and maleic anhydride illustrated above is as follows:

[0127]

[0128] The present invention also relates to pigment dispersants obtained by the preparation method of the present invention. The pigment dispersants of the present invention have excellent dispersing properties, enabling the production of pigment dispersions with high dispersion stability even with low dispersant dosage and high pigment content.

[0129] Pigment Dispersions

[0130] One object of the present invention is to provide a pigment dispersion comprising water, an inorganic pigment, and the pigment dispersant of the present invention.

[0131] Because of the use of the pigment dispersant of the present invention, the content of inorganic pigments in the pigment dispersion of the present invention is high. Preferably, based on the mass of the pigment dispersion, the content of inorganic pigments is 50% by mass or more, more preferably 55% by mass or more, for example 56% by mass, 57% by mass, 58% by mass, 59% by mass, 60% by mass, 61% by mass, 62% by mass, 63% by mass, 64% by mass, 65% by mass, 66% by mass, 67% by mass, 68% by mass, 69% by mass, or 70% by mass.

[0132] In the pigment dispersion of the present invention, the pigment dispersant is used in a low amount. Preferably, the content of the pigment dispersant is 5% by mass or less, more preferably 4% by mass or less, more preferably 3% by mass or less, even more preferably 2% by mass or less, and also, for example, 1% by mass, 0.5% by mass, 0.3% by mass, or 0.1% by mass.

[0133] The water content in the pigment dispersion of the present invention is preferably 49.9% by mass or less, more preferably 48% by mass or less, and even more preferably 45% by mass or less, for example 42% by mass, 40% by mass, 38% by mass, and 35% by mass.

[0134] This invention does not impose any particular restrictions on inorganic pigments, which can be selected according to actual needs. Preferably, the inorganic pigment is one or more selected from metal oxides, metal sulfides, chromates, and silicates; more preferably, it is one or more selected from the following: iron oxide red, iron oxide yellow, titanium dioxide, cobalt blue, cobalt green, cadmium yellow, cadmium red, chrome yellow, and ultramarine.

[0135] Without impairing the effects of the present invention, the pigment dispersion of the present invention may also contain common additives, such as one or more additives selected from the following: defoamers, pH adjusters, and anti-settling agents. The total content of additives is preferably 5% by mass or less of the pigment dispersion, more preferably 4% by mass or less, more preferably 3% by mass or less, more preferably 2% by mass or less, and also, for example, 1% by mass, 0.5% by mass, 0.3% by mass, 0.1% by mass, etc.

[0136] Examples of defoamers include, but are not limited to, silicone defoamers, polyether defoamers, mineral oil defoamers, surfactant defoamers, tributyl phosphate, alcohol defoamers, and natural oil defoamers.

[0137] Examples of pH adjusters include, but are not limited to, hydrochloric acid, sulfuric acid, acetic acid, citric acid, tartaric acid, lactic acid, sodium hydroxide, potassium hydroxide, sodium bicarbonate, ammonia, sodium carbonate, phosphate buffer, borate buffer, acetate buffer, etc.

[0138] Examples of antisettling agents include, but are not limited to, inorganic antisettling agents, polymeric antisettling agents, nonionic antisettling agents, and ionic antisettling agents.

[0139] Preferably, the pH of the pigment dispersion of the present invention is 6 to 11, more preferably 7 to 10.

[0140] This invention also relates to a method for preparing the pigment dispersion of this invention, comprising the following steps:

[0141] Mix pigment dispersant, inorganic pigment, water, and optional defoamer;

[0142] Optionally, a pH adjuster and other optional additives may be added to the resulting mixture;

[0143] Shear dispersion yields pigment dispersion.

[0144] From the perspective of improving the dispersion stability of pigment dispersions, high-speed shear dispersion is preferred, such as shear dispersion using a high-speed shear emulsifier, planetary ball mill, sand mill, or high-speed mixer. Among these, a high-speed shear emulsifier is preferred for shear dispersion, with a preferred rotation speed of 5000–20000 rpm, and more preferably 7000–15000 rpm.

[0145] Preferably, the shear dispersion time is 1–60 min, more preferably 5–40 min, and even more preferably 10–30 min.

[0146] Preferably, the preparation method of the pigment dispersion of the present invention is carried out at 10-40°C, more preferably 15-35°C.

[0147] Example

[0148] The present invention will be further illustrated below with reference to examples. These examples are for illustrative purposes only and are not intended to limit the scope of the invention. It should be understood that the present invention is not limited to the specific embodiments described below, and those skilled in the art can make various modifications or variations within the scope of the claims.

[0149] The pre-etherified light gasoline used in the following examples was purchased from Shandong Jingbo Petrochemical Co., Ltd., and its composition is shown in Table 1:

[0150] Table 1

[0151] number of carbon atoms Cycloalkanes n-Alkanes Isoalkanes Olefins Aromatics total 4 0 1.06 0.49 3.41 0 4.96 5 0.73 9.71 36.57 37.64 0 84.65 6 0.23 0.41 7.34 2.13 0.15 10.26

[0152] Note: The data in Table 1 are mass percentages (mass%), obtained by gas chromatography.

[0153] The BYK-190 solution used in the comparative examples was purchased from BYK Additives (Shanghai) Co., Ltd.

[0154] The test methods and experimental methods used in the effect evaluation of the following embodiments are described below.

[0155] Yield shear stress and viscosity at 6 rpm (η6rpm)

[0156] The apparent viscosity (η) of the pigment dispersion at 6, 10, 20, 30, 40, 50, 60, 100, 150 and 200 rpm was measured using a DV-2 viscometer. app The yield shear stress (τ) of the pigment dispersion is obtained according to the Bingham model fitting curve and equation (1). B ).

[0157] τ=τ B +η pl γ (Equation 1)

[0158] Where, τ B η is the yield shear stress of the pigment dispersion (in Pa); pl γ is the plastic viscosity (in Pa·s); γ is the shear rate (in s). -1 ) ; τ is the shear stress (unit Pa).

[0159] The apparent viscosity of the pigment dispersion at 6 rpm is the viscosity at 6 rpm (η). 6rpm The lower the viscosity at 6 rpm, the better the dispersion and wetting properties of the dispersant.

[0160] Hydrodynamic diameter (D) h ) and Zeta potential

[0161] The pigment dispersion was diluted to approximately 0.005 wt% with an aqueous sodium hydroxide solution at pH 9 ± 0.05. The hydrodynamic diameter (D) was measured using dynamic light scattering (DLS). h The zeta potential was measured by phase analysis light scattering PALS.

[0162] 48h Settlement Experiment

[0163] The pigment dispersion was placed into a 100 mL stoppered graduated cylinder, and the volume was adjusted to 100 mL. The mass (m) of the pigment dispersion was then measured. The mixture was allowed to stand at room temperature for 48 h. The volume (V) of the lower sediment was recorded. The sedimentation volume (X) was calculated according to the following formula (2), and the state of the precipitate was observed.

[0164]

[0165] In the formula:

[0166] X – The sedimentation volume of each gram of pigment in the pigment dispersion, expressed in mL / g.

[0167] V – Volume occupied by sediment, in mL

[0168] m—mass of 100 mL of dispersant sample, in g

[0169] c — the mass fraction of pigment in the pigment dispersion, expressed in (%)

[0170] Example 1

[0171] 12 g of maleic anhydride (0.122 mol) was dissolved in 80 g of isoamyl acetate. Then, 30 g of pre-etherified light gasoline (containing approximately 12 g of olefins) and 0.96 g of AIBN (5.84 mmol) were added sequentially, and the reaction was carried out at 75 °C for 8 h. After the polymerization reaction was completed, the mixture was centrifuged to obtain a solid pre-etherified gasoline-olefin-maleic anhydride copolymer. The solid was washed 3-5 times with petroleum ether to remove residual isoamyl acetate, and then dried to constant weight to obtain a white powder, PUGM-1, with a yield of approximately 30.0%.

[0172] 5 g of PUGM-1 (anhydride content of 29.8 mmol) was added to 65 mL of 1 mol / L NaOH solution, and the mixture was heated and stirred at 80 °C until the solution changed from turbid to clear. The reaction was continued for 4 h. The product was then precipitated with anhydrous ethanol, washed with anhydrous ethanol, and centrifuged three times. After drying and grinding, a pale yellow H-PUGM-1 powder was obtained, with a yield of approximately 81.1%.

[0173] Example 2

[0174] PUGM-1 was prepared in the same manner as in Example 1.

[0175] 10 g (containing 59.5 mmol of anhydride groups) of PUGM-1 was dissolved in 100 mL of ultradry dimethyl sulfoxide (DMSO). Then, 8.8 g (containing 59.5 mmol of amino groups) of sodium taurate was dissolved in 150 mL of ultradry DMSO by heating. The sodium taurate / DMSO solution was slowly added dropwise to the PUGM / DMSO solution, and the reaction was continued at 80 °C for 8 h after the addition was complete. Subsequently, a mixture of dichloromethane / n-hexane (7 / 3 v / v) was added to precipitate the product. The precipitate was centrifuged and further washed to remove residual DMSO. After drying and grinding, a light brown S-PUGM-1 powder was obtained, with a yield of 91.2%.

[0176] Example 3

[0177] 12 g of maleic anhydride (0.122 mol) was dissolved in a mixed solvent of 40 g isoamyl acetate and 45 g n-heptane. Then, 30 g of pre-etherified light gasoline (containing approximately 12 g of olefins) and 0.96 g of AIBN (5.84 mmol) were added sequentially, and the reaction was carried out at 75 °C for 8 h. After the polymerization reaction was completed, the solid pre-etherified gasoline mixed olefin-maleic anhydride copolymer was obtained by centrifugation. The solid was washed 3-5 times with petroleum ether to remove residual isoamyl acetate and n-heptane, and then dried to constant weight to obtain a white powder, PUGM-2, with a yield of approximately 50.0%.

[0178] 5 g of PUGM-2 (anhydride content of 29.8 mmol) was added to 55 mL of 1 mol / L NaOH solution, and the mixture was heated and stirred at 90 °C until the solution changed from turbid to clear. The reaction was continued for 4 h. Subsequently, the product was precipitated with anhydrous ethanol, washed with anhydrous ethanol, and centrifuged three times. After drying and grinding, a pale yellow H-PUGM-2 powder was obtained, with a yield of approximately 83.2%.

[0179] Example 4

[0180] PUGM-2 was prepared in the same manner as in Example 3.

[0181] 10 g (containing 59.5 mmol of anhydride groups) of PUGM-2 was dissolved in 90 mL of ultradry dimethyl sulfoxide (DMSO). Then, 8.8 g (containing 59.5 mmol of amino groups) of sodium taurate was dissolved in 130 mL of ultradry DMSO by heating. The sodium taurate / DMSO solution was slowly added dropwise to the PUGM / DMSO solution, and the reaction was continued at 85 °C for 7 h after the addition was complete. Subsequently, a mixture of dichloromethane / n-hexane (7 / 3 v / v) was added to precipitate the product. The precipitate was centrifuged and further washed to remove residual DMSO. After drying and grinding, a light brown S-PUGM-2 powder was obtained, with a yield of 93.0%.

[0182] Reference Example 1

[0183] Take 9g of titanium dioxide, 2 drops of BYK-024 defoamer (mass negligible, the same below) and 21g of water, mix them (solid content 30wt%), pre-stir and adjust the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), then shear and disperse them through a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T-30%.

[0184] See Example 2

[0185] Take 12g of titanium dioxide, 2 drops of BYK-024 defoamer and 18g of water and mix them (solid content 40wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed by a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T-40%.

[0186] See Example 3

[0187] Take 13.5g of titanium dioxide, 2 drops of BYK-024 defoamer and 16.5g of water and mix them (solid content 45wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed by a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T-45%.

[0188] See Example 4

[0189] Take 15g of titanium dioxide, 2 drops of BYK-024 defoamer and 15g of water and mix them (solid content 50wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed by a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T-50%.

[0190] The yield shear stress (τ) of Reference Examples 1-4 was tested according to the method described above. Β The test results are shown in Table 2.

[0191] Table 2

[0192] serial number sample Titanium dioxide solid content (wt%) <![CDATA[τ Β (Well)]]> Reference Example 1 T-30% 30 1.16 See Example 2 T-40% 40 4.41 See Example 3 T-45% 45 12.45 See Example 4 T-50% 50 20.42

[0193] As shown in Table 2, the rheological properties of the titanium dioxide dispersions prepared without dispersant in Examples 1 to 4 decrease with the increase of titanium dioxide solid content. When the titanium dioxide solid content is 50 wt%, the yield shear stress of the dispersion reaches 20.42 Pa. At this time, the fluidity of the dispersion is poor, and a dispersant needs to be added to improve the performance of the pigment dispersion.

[0194] See Example 5

[0195] Mix 40g titanium dioxide, 1g BYK-190 solution (0.4g active ingredient, accounting for 1wt% of pigment mass), 2 drops BYK-024 defoamer and 19g water (solid content is 66.7wt%), pre-stir and adjust pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), then shear and disperse through a high-speed shear emulsifier at 10000rpm for 20min.

[0196] See Example 6

[0197] Mix 40g titanium dioxide, 1g BYK-190 solution (active ingredient accounts for 1wt% of pigment mass), 2 drops BYK-024 defoamer and 19g water (solid content is 66.7wt%), pre-stir and adjust pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), then shear disperse through a planetary ball mill at 800rpm for 10min each of forward and reverse rotation.

[0198] The hydrodynamic diameter (D) of the dispersions obtained in Examples 5 and 6 were tested according to the method described above. h ) and Zeta potential, the results are as follows Figure 1 As shown. By Figure 1 It is known that the hydrodynamic diameter (D) of the dispersions prepared in Reference Examples 5 and 6 is... h The difference between the α and β potentials is not significant, indicating that high-speed shearing and ball milling have little impact on the dispersion effect of the pigment dispersion.

[0199] Comparative Example 1

[0200] Mix 30g titanium dioxide, 0.75g BYK-190 solution (0.3g active ingredient, accounting for 1% of the pigment mass), 2 drops of BYK-024 defoamer, and 19.25g water (solid content 60wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T60%-B1%.

[0201] Comparative Example 2

[0202] Mix 30g titanium dioxide, 2.25g BYK-190 solution (0.9g active ingredient, accounting for 3% of the pigment mass), 2 drops BYK-024 defoamer, and 17.75g water (solid content 60wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T60%-B3%.

[0203] Comparative Example 3

[0204] Mix 30g titanium dioxide, 3.75g BYK-190 solution (1.5g active ingredient, accounting for 5% of the pigment mass), 2 drops of BYK-024 defoamer, and 16.25g water (solid content 60wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T60%-B5%.

[0205] Comparative Example 4

[0206] Mix 30g titanium dioxide, 7.5g BYK-190 solution (3g of active ingredient, accounting for 10% of the pigment mass), 2 drops of BYK-024 defoamer, and 12.5g water (solid content 60wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T60%-B10%.

[0207] Comparative Example 5

[0208] Mix 30g titanium dioxide, 11.25g BYK-190 solution (4.5g active ingredient, accounting for 15% of the pigment mass), 2 drops of BYK-024 defoamer, and 8.75g water (solid content 60wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T60%-B15%.

[0209] The hydrodynamic diameter (D) of the dispersions obtained in Comparative Examples 1–5 was tested according to the method described above. h Zeta potential, yield shear stress (τ) B ) and viscosity at 6 rpm (η) 6rpm The results are shown in Table 3.

[0210] Table 3

[0211] serial number sample <![CDATA[D h (nm)]]> Zeta potential (mV) <![CDATA[τ B (Well)]]> Η(mPa·s) Comparative Example 1 T60%-B1% 270.6±3.0 -24.9±0.5 4.31 584.0 Comparative Example 2 T60%-B3% 261.6±3.3 -26.6±0.3 3.92 550.8 Comparative Example 3 T60%-B5% 255.6±1.5 -27.3±0.8 2.91 359.9 Comparative Example 4 T60%-B10% 254.6±2.4 -30.9±0.4 6.37 768.6 Comparative Example 5 T60%-B15% 252.6±3.5 -32.1±0.9 7.39 1070.1

[0212] According to the results in Table 3, when the solid content of titanium dioxide is 60 wt%, the hydrodynamic diameter and zeta potential of the dispersion do not change significantly with the increase of BYK-190 content, but τ B With η 6rpm It shows a trend of first decreasing and then increasing. When the content of BYK-190 is 5wt%, τ B The Pa is 2.91, and η 6rpmThe rheological properties of the dispersion are optimal at 359.9 mPa·s.

[0213] Example 5

[0214] 30.5g of titanium dioxide, 0.305g of H-PUGM-1 obtained in Example 1 (1% of the pigment mass), 2 drops of BYK-024 defoamer, and 19.195g of water were mixed (solid content was 61wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture was sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion was denoted as T61%-H1%.

[0215] Example 6

[0216] 31.5g of titanium dioxide, 0.315g of H-PUGM-1 obtained in Example 1 (1% of the pigment mass), 2 drops of BYK-024 defoamer, and 18.185g of water were mixed (solid content was 63wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture was sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion was denoted as T63%-H1%.

[0217] Example 7

[0218] 32.5g of titanium dioxide, 0.325g of H-PUGM-1 obtained in Example 1 (1% of the pigment mass), 2 drops of BYK-024 defoamer, and 17.175g of water were mixed (solid content was 65wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture was sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion was denoted as T65%-H1%.

[0219] Example 8

[0220] 33.5g of titanium dioxide, 0.335g of H-PUGM-1 obtained in Example 1 (1% of the pigment mass), 2 drops of BYK-024 defoamer, and 16.165g of water were mixed (solid content was 67wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture was sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion was denoted as T67%-H1%.

[0221] Example 9

[0222] 35g of titanium dioxide, 0.35g of H-PUGM-1 obtained in Example 1 (1% of the pigment mass), 2 drops of BYK-024 defoamer, and 14.65g of water were mixed (solid content was 70wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture was sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion was denoted as T70%-H1%.

[0223] The D of the dispersions obtained in Examples 5-9 were tested according to the method described above. h Zeta potential, τ B and η 6rpm The results are shown in Table 4.

[0224] Table 4

[0225] serial number sample <![CDATA[D h (nm)]]> Zeta potential (mV) <![CDATA[τ B (Well)]]> <![CDATA[η 6rpm (mPa·s)]]> Example 5 T61%-H1% 330.1±1.7 -23.0±0.4 1.88 260.4 Example 6 T63%-H1% 290.2±3.1 -23.0±0.3 2.86 350.4 Example 7 T65%-H1% 305.6±1.9 -19.4±1.0 4.41 576.1 Example 8 T67%-H1% 283.8±2.8 -23.3±0.7 7.33 871.2 Example 9 T70%-H1% 282.0±6.0 -21.9±0.7 13.16 1220.0

[0226] According to Table 4, when the content of dispersant H-PUGM-1 is 1% of the pigment mass, τ B and η 6rpm The value increases with the increase of titanium dioxide solid content. When the titanium dioxide solid content is 63 wt%, τ... B The Pa is 2.86, and η 6rpm The stress is 350.4 mPa·s, at which point the dispersion still exhibits good rheological properties even with the highest possible titanium dioxide solid content.

[0227] Example 10

[0228] Mix 30.5g titanium dioxide, 0.305g S-PUGM-1 (1% of pigment mass), 2 drops of BYK-024 defoamer, and 19.195g water (solid content 61wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T61%-S1%.

[0229] Example 11

[0230] Mix 31.5g titanium dioxide, 0.315g S-PUGM-1 (1% of pigment mass), 2 drops of BYK-024 defoamer, and 18.185g water (solid content 63wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T63%-S1.

[0231] Example 12

[0232] Mix 32.5g titanium dioxide, 0.325g S-PUGM-1 (1% of pigment mass), 2 drops of BYK-024 defoamer, and 17.175g water (solid content 65wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T65%-S1%.

[0233] Example 13

[0234] Mix 33.5g titanium dioxide, 0.335g S-PUGM-1 (1% of pigment mass), 2 drops of BYK-024 defoamer, and 16.165g water (solid content 67wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T67%-S1.

[0235] Example 14

[0236] Mix 35g titanium dioxide, 0.35g S-PUGM-1 (1% of pigment mass), 2 drops of BYK-024 defoamer, and 14.65g water (solid content 70wt%). After pre-stirring and adjusting the pH to 9±0.05 with sodium hydroxide aqueous solution (1mol / L), the mixture is then sheared and dispersed using a high-speed shear emulsifier at 10000rpm for 20min. This dispersion is denoted as T70%-S1.

[0237] The D of the dispersions obtained in Examples 10-14 was determined according to the method described above. h Zeta potential, τ B and η 6rpm The results are shown in Table 5.

[0238] Table 5

[0239] serial number sample <![CDATA[D h (nm)]]> Zeta potential (mV) <![CDATA[τ B (Well)]]> <![CDATA[η 6rpm (mPa·s)]]> Example 10 T61%-S1% 267.2±2.0 -20.7±0.5 2.06 232.0 Example 11 T63%-S1% 255.7±2.6 -22.4±0.6 1.65 260.4 Example 12 T65%-S1% 258.8±4.6 -21.8±0.2 1.95 262.0 Example 13 T67%-S1% 262.3±5.2 -18.5±0.4 5.49 614 Example 14 T70%-S1% 275.8±3.5 -19.6±0.9 11.67 801.8

[0240] According to the results in Table 5, when the content of dispersant S-PUGM-1 is 1% of the pigment mass, the D of the dispersion... h As the solid content of titanium dioxide increased, the particle size remained below 300 nm, indicating that the pigment particles in these dispersions were uniformly dispersed. B and η 6rpm The τ value will initially remain stable and then gradually increase with increasing titanium dioxide solid content. When the titanium dioxide solid content is 65 wt%, τ BThe Pa is 2.86, and η 6rpm The stress is 350.4 mPa·s, at which point the dispersion still exhibits excellent rheological properties despite the high solid content of titanium dioxide.

[0241] Photographs of the 48-hour settlement experiment of Comparative Example 3, Example 6, and Example 12 are shown below. Figure 2 As shown, the results are presented in Table 6. In Table 6, D... h-48 The hydrodynamic diameter is obtained by testing the dispersion after a 48-hour settling experiment.

[0242] Table 6

[0243] serial number sample X (mL / g) <![CDATA[D h-48 (nm) <!-- 14 -->]]> Comparative Example 3 T60%-B5% 0.94 259±4.0 Example 12 T65%-S1% 0.86 265±4.5 Example 6 T63%-H1% 0.87 263±2.7

[0244] Based on the results in Tables 3, 4, 5, and 6, compared to Comparative Example 3 (T60%-B5%), with comparable dispersion stability and rheological properties, the dispersants S-PUGM-1 and H-PUGM-1 of the present invention used in Example 12 (T65%-S1%) and Example 6 (T63%-H1%) can disperse more pigment with less dispersant content, indicating that S-PUGM-1 and H-PUGM-1 can be used as highly efficient pigment dispersants, with S-PUGM-1 being more effective.

[0245] The dispersion of the dispersions in Reference Example 4, Comparative Example 3, Example 6, and Example 12 was observed using transmission electron microscopy (TEM). The TEM images are shown below. Figure 3 As shown in (a) to (d). From Figure 3 It can be seen that without the addition of a dispersant (refer to Example 4), the titanium dioxide particles formed large agglomerates; while with the addition of BYK-190 (Comparative Example 3), S-PUGM-1 (Example 12) and H-PUGM-1 (Example 6), the titanium dioxide particles were smaller and no large agglomerates were observed. Examples 6 and 12 achieved dispersion effects comparable to Comparative Example 3.

[0246] Industrial applicability

[0247] The method for preparing pigment dispersions of the present invention can be widely used to reduce the olefin content of light gasoline before etherification in petrochemical enterprises, and can also be widely used to prepare pigment dispersions of inorganic pigments.

Claims

1. A method for preparing a pigment dispersant, characterized in that, Includes the following steps: (1) The light gasoline before etherification and maleic anhydride are subjected to self-stabilizing precipitation polymerization in an organic solvent to obtain a mixed olefin-maleic anhydride copolymer. (2) The mixed olefin-maleic anhydride copolymer is functionalized and modified; The functional modification is either (i) hydrolysis modification or (ii) sulfonation modification: (i) Hydrolysis modification: hydrolyzing the maleic anhydride groups in the mixed olefin-maleic anhydride copolymer. (ii) Sulfonation modification: reacting the mixed olefin-maleic anhydride copolymer with a sulfonic acid compound having hydroxyl or amino groups.

2. The preparation method according to claim 1, characterized in that, In the (i) hydrolysis modification, the hydrolysis is carried out in an alkaline aqueous solution, wherein the alkaline is preferably sodium hydroxide and / or potassium hydroxide, and the concentration of the alkaline aqueous solution is 0.1 to 5 mol / L.

3. The preparation method according to claim 1, characterized in that, In the sulfonation modification described in (ii), the sulfonic acid compound having hydroxyl or amino groups is selected from one or more of aminosulfonic acid, alkylaminosulfonic acid, arylaminosulfonic acid, aminoalkylsulfonic acid, aminoarylsulfonic acid, hydroxyalkylsulfonic acid, hydroxyarylsulfonic acid, hydroxyalkylaminosulfonic acid, and their salts. Preferably, the sulfonic acid compound having a hydroxyl or amino group is selected from one or more of the following: aminosulfonic acid, N-methylaminosulfonic acid, ethylaminosulfonic acid, aminomethanesulfonic acid, taurine, aminopropanesulfonic acid, 2-aminobenzenesulfonic acid, 3-aminobenzenesulfonic acid, 4-aminobenzenesulfonic acid, aminonaphthalenesulfonic acid, (3-hydroxypropyl)aminosulfonic acid, 3-hydroxypropanesulfonic acid, 4-hydroxybutyric acid, 4-hydroxybenzenesulfonic acid, m-hydroxybenzenesulfonic acid, hydroxyethylsulfonic acid, 8-hydroxynaphthalene-1-sulfonic acid, and their salts; The molar ratio of maleic anhydride groups in the mixed olefin-maleic anhydride copolymer to the sulfonic acid compound having hydroxyl or amino groups is 1:(0.1-3). The reaction of the mixed olefin-maleic anhydride copolymer with a sulfonic acid compound having hydroxyl or amino groups is carried out in an aprotic dipole solvent.

4. The preparation method according to claim 1, characterized in that, In step (1), the organic solvent includes an alkyl ester of an organic acid, which preferably has the following structure: Wherein R1 is H or a hydrocarbon group having 1 to 8 C atoms, and R2 is an alkyl group having 1 to 5 C atoms; Preferably, the organic solvent further includes alkanes, and the mass ratio of the organic acid alkyl ester to the alkanes is 1:(0.1-3).

5. The preparation method according to claim 1, characterized in that, In step (1), the mass ratio of maleic anhydride to etherified light gasoline is 1:(1-5); The total content of maleic anhydride and pre-etherified light gasoline in the reaction system is 10-50% by mass, where "reaction system" refers to the system composed of maleic anhydride, pre-etherified light gasoline, organic solvent, and initiator.

6. A pigment dispersant obtained by the preparation method according to any one of claims 1 to 5.

7. A pigment dispersion, characterized in that, Includes water, inorganic pigments, and the pigment dispersant according to claim 6.

8. The pigment dispersion according to claim 7, characterized in that, The content of the inorganic pigment is more than 50% by mass of the pigment dispersion; the amount of the pigment dispersant is less than 5% by mass of the inorganic pigment.

9. The pigment dispersion according to claim 7 or 8, characterized in that, The inorganic pigment is selected from one or more of metal oxides, metal sulfides, chromates, and silicates; preferably selected from one or more of the following: iron oxide red, iron oxide yellow, titanium dioxide, cobalt blue, cobalt green, cadmium yellow, cadmium red, chrome yellow, and ultramarine.

10. The pigment dispersion according to claim 7 or 8, characterized in that, It also includes one or more additives selected from the following: defoamers, pH adjusters, and antisettling agents.